2011
DOI: 10.1038/emboj.2011.291
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of the Ras-like G protein MglA and its cognate GAP MglB and implications for bacterial polarity

Abstract: Structural analysis of the Ras-like G protein MglA and its cognate GAP MglB and implications for bacterial polarityThe small G protein MglA and its cognate GAP MglB exemplify a new type of GTPase activation mechanism. In contrast to other Ras-like proteins, the key 'arginine finger' is provided not by the GAP, but by MglA itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
158
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(168 citation statements)
references
References 66 publications
10
158
0
Order By: Relevance
“…In contrast, MglA did not appear to form oligomers, because the Escherichia coli strain carrying pUT18-mglA and pKTN25-mglA did not turn blue. This observation is consistent with the deduced crystal structure that shows one molecule of MglA forming a complex with two molecules of MglB (25).…”
Section: Single Gliding Motors Frequently Reverse Their Direction Of supporting
confidence: 80%
“…In contrast, MglA did not appear to form oligomers, because the Escherichia coli strain carrying pUT18-mglA and pKTN25-mglA did not turn blue. This observation is consistent with the deduced crystal structure that shows one molecule of MglA forming a complex with two molecules of MglB (25).…”
Section: Single Gliding Motors Frequently Reverse Their Direction Of supporting
confidence: 80%
“…For M. xanthus it was shown that this relocation of the ATPase requires parts of the cytoskeleton and a Ras-like G protein, MglA, and its cognate GTPase-activating protein (GAP), MglB (38). Proteins that show homologies to these proteins were also found in T. thermophilus and might be also required for the relocation of PilF from T. thermophilus (41). The multiple cysteine mutations in the tetracysteine motif and the absence of zinc in the mutant PilF complexes might have a significant effect on the structure of the PilF complexes and/or the transfer of structural changes through the PilF complex, thereby affecting the interaction of PilF complexes with cytoskeletal components.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, the KaiC-centered signaling systems could be interconnected with other signal transduction pathways, in particular, with two-components systems, via shared domains of input proteins (Fig. 4), and with Ras-like GTPases, either directly through the interaction with Srp102/FtsY or through Roadblock family proteins as described for both bacteria and eukaryotes (58,59). The mode of signaling apparently Below the scheme of predicted protein-protein interaction, selected input, modulator, and output components are listed inside the oval borders, which are colored according to the predicted functions of these components.…”
Section: Resultsmentioning
confidence: 99%